Electric Response and Conductivity Mechanism in H3PO4‑Doped Polybenzimidazole-4N−HfO2 Nanocomposite Membranes for High Temperature Fuel Cells. (20th February 2017) - Nawn, Graeme; Vezzù, Keti; Bertasi, Federico; Pagot, Gioele; Pace, Giuseppe; Conti, Fosca; Negro, Enrico; Di Noto, Vito
Abstract: Relaxation and polarization phenomena of phosphoric acid-doped [PBI4N(HfO2 )x ](H3 PO4 )y nanocomposite membranes for high-temperature proton-exchange membrane fuel cells are studied using Dynamic Mechanical Analysis (DMA) and Broadband Electrical Spectroscopy (BES). The membranes are obtained by casting combinations of a polybenzimidazole polymer (PBI4N) with increasing amounts of hafnium oxide nanofiller, resulting in [PBI4N(HfO2 )x ] hybrid systems with 0 ≤ x ≤ 0.32. Phosphoric acid at varying content levels (0 ÷ 18 wt%) is used as a doping agent, giving rise to [PBI4N(HfO2 )x ](H3 PO4 )y membranes. DMA and BES studies lead us to determine that the electric response of the membranes is modulated by polarization phenomena and by α and β dielectric relaxation events of the polymer matrix. Additionally, the experimental results suggest that in [PBI4N(HfO2 )x ](H3 PO4 )y membranes the conductivity occurs owing to three conductivity pathways: two mechanisms involving inter-domain proton migration phenomena by "hopping" events; and one mechanism in which proton exchange occurs between delocalization bodies. These results highlight the significant effect of the hafnium oxide nanofiller content on the conductivity of [PBI4N(HfO2 )x ](H3 PO4 )y where, at x ≥ 0.04, demonstrates conductivity higher (9.0 × 10 −2  S/cm) than that of pristine H3 PO4 -doped PBI4N (4.8 × 10 −2  S/cm) at T ≥ 155 °C.